Video Design Motion Graphic Based Company Profile as Publication Media Pt. Muliaoffset Packindo Semarang City: Case study: PT. Muliaoffset Packindo Semarang - Lukas Dwi Santoso; Sarwo Nugroho (International Journal of Graphic Design, 2024)
Competition in the business world is getting tougher day by day. The increasing market demand for product requirements has triggered the emergence of new companies that continue to grow. Because of this, good and communicative marketing is needed as a means of introducing the company to consumers so that the company or business being run can be widely known and continue to compete with other competitors. Publication media is currently increasingly varied and interesting. Technological advances indirectly force graphic designers to continue to develop and produce work that is fresh and up to dateThere are more and more innovations and significant developments in the world of publications as time goes by. Unlike before, today's publication media is dominated by non-print media. Before the widespread use of the internet and smartphones , publication media was dominated by print media such as; brochures, posters, billboards, banners and other printed media. Ease of access is one of the main factors causing the rise of non-physical publication media. Information about a company can be accessed more easily and practically, compared to using print media which is starting to be replaced. Company profile videos This contains, among other things ; company background, address, telephone number, email , website , and other information that needs to be displayed about PT. Muliaoffset Packindo. Videos company profile Motion graphic- based has a relatively short duration but is packaged in an interesting way, because of the movement animations and transitions applied to each frame. After seeing the company's company profile video , the audience expects interested with the information presented and get to know more about the company .